Parental smoking and exposure to environmental tobacco smoke are associated with waterpipe smoking among youth: results from a national survey in Lebanon. Issue 4 (April 2015) - Jawad, M.; Nakkash, R.T.; Mahfoud, Z.; Bteddini, D.; Haddad, P.; Afifi, R.A.
Abstract Objectives Waterpipe tobacco smoking (WTS) is a growing public health concern worldwide yet little is known about the epidemiology of use among young people. The objectives of this study were to examine the prevalence, patterns and correlates of WTS among students across Lebanon. Study design The study design was a cross sectional survey. Methods 126-item tobacco questionnaire was conducted among 1128 sixth and seventh grade students across Lebanon. Current patterns of use were descriptively analysed, and logistic regression models examined correlates of WTS. Results Ever WTS prevalence was 44.3%, current WTS prevalence was triple that of cigarettes (22.1% vs 7.4%), and 40.0% of current users were at least weekly or daily smokers. Initiation and patterns of use, as well as addiction and cessation attitudes have been reported. Significant correlates of current WTS included older age, reduced religiosity, peer and parent tobacco use, recent waterpipe advertisement exposure, increased pluralistic ignorance and current cigarette use. Significant correlates of ever WTS were similar to current WTS, but included second hand waterpipe tobacco smoke exposure at home and did not include recent waterpipe advertisement exposure. Neither gender nor socio-economic status were significant correlates of current or ever WTS. Conclusions Waterpipe is the most common form of tobacco smoking, and is used regularly, among sixth and seventh grade Lebanese students. It should be considered a public health priority with increased tobacco surveillance and legislation. Widespread educational and policy interventions might help denormalize the social acceptability of WTS. Meanwhile, more research is needed to understand the changing paradigm of WTS epidemiology and the health outcomes among young smokers.